Climate‐driven evolutionary change in reproductive and early‐acting life‐history traits in the perennial grass Festuca ovina. (11th May 2020) - Trinder, Sarah; Askew, Andrew P.; Whitlock, Raj
Abstract: Reproductive and early‐acting life‐history traits are likely to be particularly important determinants of plant fitness under a changing climate. There have, however, been few robust tests of the evolution of these traits under chronic climate change in natural ecosystems. Such studies are urgently needed, to evaluate the contribution of evolutionary change to population persistence. Here, we examine climate‐driven evolutionary change in reproductive and early‐acting plant life‐history traits in the long‐lived perennial plant, Festuca ovina . We collected established plants of F. ovina from species‐rich calcareous grassland at the Buxton Climate Change Impacts Laboratory (BCCIL), after 17 years of in situ experimental drought treatment. P1 plants collected from drought‐treated and control (ambient climate) plots at BCCIL were used to create an open‐pollinated F1 progeny array, which was subsequently validated using microsatellite markers to establish a robust bi‐parental pedigree. We measured the timing of germination and seed mass in the F1 progeny, the P1 paternal contribution to F1 offspring (paternal reproductive success), and assessed the effects of flowering time on the mating system. F1 seed with ancestry in drought‐treated plots at BCCIL germinated significantly later than seed derived from individuals from control plots. P1 plants from the drought treatment flowered significantly earlier than those from the control plots in summer 2012, but not in 2013. Male reproductive success was also lower in P1 plants collected from drought plots than those from control plots. Furthermore, our pedigree revealed that mating among parents of the F1 progeny had been assortative with respect to flowering time. Synthesis . Our study shows that chronic drought treatment at Buxton Climate Change Impacts Laboratory has driven rapid evolutionary change in reproductive and early‐acting life‐history traits in Festuca ovina, and suggests that evolutionary differentiation may be reinforced through changes in flowering time that reduce the potential for gene flow. Abstract : Our study shows that chronic drought treatment at Buxton Climate Change Impacts Laboratory has driven rapid evolutionary change in reproductive and early‐acting life‐history traits in F. ovina, and suggests that evolutionary differentiation may be reinforced through changes in flowering time that reduce the potential for gene flow.